2009
DOI: 10.1590/s0036-36342009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Suicide notes from Mexico and the United States: a thematic analysis

Abstract: Suicide notes from Mexico and the United States: a thematic analysis. Salud Publica Mex 2009;51:314-320. AbstractObjective. This study sought to investigate suicide notes drawn from Mexico and the United States (US) as these countries share geographical proximity, but markedly different cultures and suicide rates. Material and Methods. A theoretical conceptual analysis of 102 suicide notes drawn from these countries, matched for age and sex, was undertaken based on a thematic model of suicide developed by Leen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Both content and thematic analyses have been conducted on suicide notes to identify certain themes which emerge within different types of suicide notes, with varying levels of success (Chávez‐Hernández, Leenaars, Chávez‐de Sánchez, & Leenaars, ; Ioannou & Debowska, ; O'Connor et al., ). Handelman and Lester () looked at the content of notes left by attempters and completers of suicide and found that the data obtained from suicide notes of those who completed the act showed that their notes were more likely to have references to other people, and fewer references to inclusive space (e.g., words such as “with” or “include”).…”
Section: The Concept Of Suicidementioning
confidence: 99%
“…Both content and thematic analyses have been conducted on suicide notes to identify certain themes which emerge within different types of suicide notes, with varying levels of success (Chávez‐Hernández, Leenaars, Chávez‐de Sánchez, & Leenaars, ; Ioannou & Debowska, ; O'Connor et al., ). Handelman and Lester () looked at the content of notes left by attempters and completers of suicide and found that the data obtained from suicide notes of those who completed the act showed that their notes were more likely to have references to other people, and fewer references to inclusive space (e.g., words such as “with” or “include”).…”
Section: The Concept Of Suicidementioning
confidence: 99%
“…Suicide note studies are still scarce in Latin America; Among the first reported are those conducted in Mexico studying general population (Chávez-Hernández, 1988;Chávez-Hernández & Macías-García, 2007;Chávez-Hernández, Macías-García, & Luna-Lara, 2011) and one that focused on suicide notes left by children (Páramo-Castillo & Chávez-Hernández, 2007). Studies comparing Mexican and international samples have also been conducted (Chávez-Hernández et al, 2006;Chávez-Hernández, Leenaars, Chávez-de-Sánchez, & Leenaars, 2009).…”
Section: Suicide Notes Studies In Latin Americamentioning
confidence: 99%
“…For some of our patients that pain becomes unbearable, and it is hardly surprising that psychological pain is the most often mentioned reason for suicide (Chavez-Hernandez, Leenaars, Chavez-de Sanchez, & Leenaars, 2009). For example, due to a pervasive illness or break-up of a romantic relationship, due to the prospect of losing a loved one because of a terminal disease, or due to old age that may come with a declining support system and social isolation.…”
mentioning
confidence: 96%